Acute lymphoblastic Leukaemia in Sri Lankan children: a 10 year experience at National Cancer Institute , Sri Lanka. - Siriwardena, P.A.V (My University, 1995)
The study was undertaken to evaluate patient characteristics, (age and sex distribution) long term sequelae of CNS prophylaxis (growth retardation) and the treatment outcome in these 66 paediatric patients who were treated and followed up at cancer institute, Maharagama, Sri Lanka during the period between 1st May 1982 and 27 th September 1993. Two of them expired within this 11 year period of follow up of CNS leukaemia.The majority of children belonged to 3 to 6 year age group with 64 per cent of cases. The treatment given had been the standard treatment for acute lymphoblastic leukaemia during the period concerned